1993
DOI: 10.1002/pro.5560021006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single aspartate on helix stability at different positions in a neutral alanine‐based peptide

Abstract: A single aspartate residue has been placed at various positions in individual peptides for which the alanine-based reference peptide is electrically neutral, and the helix contents of the peptides have been measured by circular dichroism. The dependence of peptide helix content on aspartate position has been used to determine the helix propensity (s-value). Both the charged (Asp-) and uncharged (Asp') forms of the aspartate residue are strong helix breakers and have identical s-values of 0.29 at 0 "C. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
138
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 31 publications
(50 reference statements)
19
138
0
Order By: Relevance
“…Interestingly, then, these observations mirror the fraying behavior at the ends of helices that has been reported for isolated, short helical peptides. 23,24 Under conditions very far from unfolding, most amide HX may be ascribed to local fluctuations, which likely involve breaking individual hydrogen bonds. Such reactions occur very infrequently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, then, these observations mirror the fraying behavior at the ends of helices that has been reported for isolated, short helical peptides. 23,24 Under conditions very far from unfolding, most amide HX may be ascribed to local fluctuations, which likely involve breaking individual hydrogen bonds. Such reactions occur very infrequently.…”
Section: Resultsmentioning
confidence: 99%
“…This predicted end-fraying effect is analogous to the behavior observed for short monomeric peptides. 23,24 Such peptides show a distribution of helical and non-helical conformations, with the central residues having the highest probability of being helical, while the ends fray. The behavior of helical peptides has long been known to be well described by an Ising model treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The reference and test peptides are treated by assigning an average intrinsic helix propensity, 〈w〉 host , to alanine and lysine residues. The other residues are given previously determined w and n (n-cap) values (Armstrong & Baldwin, 1993;Huyghues-Despointes et al, 1993a;Doig et al, 1994), which have been revised recently by Rohl et al (1996) …”
Section: Synthesis Of Peptides Purification and CD Measurementsmentioning
confidence: 99%
“…The charge states are often correlated to the structures, properties, and biological functions of the proteins. Studies have shown that charged groups close to the ends of helices were found to be an important determinant of the stability of the helices [2][3][4][5][6]. The extents of protonation and deprotonation are directly related to the acid-base properties of individual amino acid residues.…”
mentioning
confidence: 99%
“…Interestingly, an amino acid residue located at different positions in a folded protein often exhibits different degrees of acidity or basicity. For example, an acidic residue, such as cysteine or aspartic acid, located at or near the N-terminus of a helix is often more acidic than that at or near the C-terminus [5,[7][8][9][10][11]. A wealth of studies on the acid-base properties of helical peptides have been carried out in condensed phase, in particular in aqueous solutions [11][12][13].…”
mentioning
confidence: 99%